2013
DOI: 10.1016/j.ejc.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Proof of Moll’s minimum conjecture

Abstract: Let d i (m) denote the coefficients of the Boros-Moll polynomials. Moll's minimum conjecture states that the sequence {iThis conjecture is a stronger than the log-concavity conjecture proved by Kausers and Paule. We give a proof of Moll's conjecture by utilizing the spiral property of the sequence {d i (m)} 0≤i≤m , and the log-concavity of the sequence {i!d i (m)} 0≤i≤m .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
3
4
0
Order By: Relevance
“…Recently, Chen and Xia [13] showed that the sequence {d i (m)} 0≤i≤m satisfies the strongly ratio monotone property which implies the logconcavity and the spiral property. They [14] also confirmed a conjecture of Moll which says that…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Recently, Chen and Xia [13] showed that the sequence {d i (m)} 0≤i≤m satisfies the strongly ratio monotone property which implies the logconcavity and the spiral property. They [14] also confirmed a conjecture of Moll which says that…”
Section: Introductionsupporting
confidence: 71%
“…By comparing the first entry with the last entry, we deduce that this sequence attains its minimum at i = m, which equals 2 −2m m(m + 1) 2m m 2 . This conjecture was confirmed by Chen and Xia [12] by using a result of Chen and Gu [10] and the spiral property of the Boros-Moll sequences [11].…”
Section: Theorem 14 the Boros-moll Sequences Arementioning
confidence: 55%
“…Chen and Xia [13] proved that the Boros-Moll sequences satisfy the ratio monotone property which implies the log-concavity and the spiral property. They [14] also confirmed a conjecture given by Moll in [19]. By constructing an intermediate function, Chen and Xia [15] proved the 2-log-concavity of the Boros-Moll sequences.…”
Section: Introduction and Main Resultssupporting
confidence: 79%
“…Recently, Chen and Xia [ 4 ] showed that the sequence satisfies the strongly ratio monotone property which implies the log-concavity and the spiral property. They [ 5 ] also confirmed a conjecture of Moll which says that attains its minimum at . Chen et al [ 6 ] proved that the Boros-Moll sequences are interlacing log-concave.…”
Section: Introduction and Main Resultssupporting
confidence: 53%